511. What Is the Current State of Patient Education after Clostridium difficile Infection?. (26th November 2018) - DeBenedictus, Christina; John, Jacob; Hecker, Michelle; Donskey, Curtis J; Patel, Payal K
Abstract: Background: Clostridium difficile infection (CDI) is a common healthcare-associated infection that often recurs after treatment and is associated with reduced quality of life. High-quality patient engagement and education could reduce the risk for transmission and reinfection. Methods: We surveyed 18 institutions, including academic, Veterans Affairs, and community hospitals, to evaluate if they had CDI-specific patient education practices in place. For three of the institutions, we surveyed CDI patients immediately after hospital discharge regarding the CDI education provided and assessed their knowledge of patient-based prevention measures. Results: Of the 15 hospitals responding to the survey, 11 (73%) reported having standardized written educational materials regarding CDI. However, Infection Prevention personnel from four (27%) of these hospitals were not confident that the education was being implemented and five (33%) were not confident that the patients understood the education. Of 24 CDI patients surveyed, only 13 (54%) reported receiving any education about CDI from hospital personnel, and only three(12.5%) reported receiving written information. Seven of the 24 (29%) CDI patients reported looking up information online about CDI. Of the 24 CDI patients, three(12.5%) were not aware that soap and water should be used for hand hygiene, 7 (29%) were not aware that bleach should be used for cleaning their bathroom, and 13 (54%) did not choose taking antibiotics as the major risk for recurrence. Conclusion: Although most hospitals reported having standardized educational materials for CDI patients, our survey of patients demonstrated substantial deficiencies in the education provided and in patients' knowledge of CDI prevention measures. Engagement of CDI patients in prevention efforts will require improvement in education practices. Disclosures: All authors: No reported disclosures.